TI_GERICHTE 11.2011.142 vom 20. Dezember 2012 , Contestazione di una risoluzione assembleare: procedura di conciliazione - TI Tribunale d'appello (2012)
Contestazione di una risoluzione assembleare: procedura di conciliazione